Integration of an anti-tumor drug into nanocrystalline assemblies for sustained drug release1. Issue 3 (16th March 2015) - Yang, Xiangrui; Wu, Shichao; Li, Yang; Huang, Yu; Lin, Jinyan; Chang, Di; Ye, Shefang; Xie, Liya; Jiang, Yuan; Hou, Zhenqing
<x xml:space="preserve">Abstract</x> A bio-inspired approach was used to integrate an anti-tumor drug into nanocrystalline assemblies for sustained drug release.